Gastrointestinal Granular Cell Tumor: The First Report of a Multifocal and Potentially Hereditary Case - Riccardo Sigon; Lisa Fusaro; Fabio Monica; Michele Campigotto (Gastroenterology Insights, 2024)
Granular cell tumors (GCTs), also known as Abrikossoff tumors, are rare tumors that originate from Schwann cells that primarily localize in the tongue, skin and submucosal tissues and involve the gastrointestinal tract in 11% of cases. We present a case of a young woman who first presented to our center in 2018 for an EGDS to assess a thickening of the esophageal wall, seen on a CT. On that occasion, a diagnosis of Abrikossoff tumor was made. She underwent endoscopic resection with subsequent yearly follow-up without evidence of recurrence. Five years later, during a routine colonoscopy, we found numerous white submucosal formations in all of the explored tracts, with a histological examination compatible with GCTs. Her daughter presented with a white nodule on her tongue, also diagnosed as a GCT. Her daughter was also diagnosed with a GCT of the tongue a few months later. Our research represents a significant contribution to the field given that it presents the first documented case of a patient with multifocal gastrointestinal GCTs and suggests a potential hereditary component.